2009
DOI: 10.1590/s0073-47212009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Suscetibilidade de operárias e larvas de abelhas sociais em relação à ricinina

Abstract: ABSTRACT. Susceptibility of workers and larvae of social bees in relation to ricinine. Many substances of vegetal origin can be toxic or present an insecticidal potential. With the aim of decreasing the environment pollution problem, a few studies are trying to substitute synthetic insecticides with botanical ones. Ricinus communis (Euphorbiaceae) presents a great variety of substances, being the ricinine the main toxic component. Considering that bees are useful as pollinator agents of plants, this study eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Hebling 19 , assessed the bioactivity of R. communis on ants and demonstrated its effi cacy in combating Hymenopteran, Burg and Mayer 20 tested the effect of R. communis seed oil on aphids and different species of lice, describing how promising this oil was for the control of these insects. In a study of the effects of aqueous extract from the green fruits of castor on the larvae and pupae of Spodoptera frugiperda, Santiago 21 observed a reduction in the lifetime of these stages, and Rother 22 identifi ed toxic effects of leaf extracts of R. communis on Apis mellifera worker larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Hebling 19 , assessed the bioactivity of R. communis on ants and demonstrated its effi cacy in combating Hymenopteran, Burg and Mayer 20 tested the effect of R. communis seed oil on aphids and different species of lice, describing how promising this oil was for the control of these insects. In a study of the effects of aqueous extract from the green fruits of castor on the larvae and pupae of Spodoptera frugiperda, Santiago 21 observed a reduction in the lifetime of these stages, and Rother 22 identifi ed toxic effects of leaf extracts of R. communis on Apis mellifera worker larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated pest management programs determine which insecticides are compatible with a biological control agent and to identify the possible effect on them [32]. Biopesticide studies are frequent in an attempt to reduce the ecological impact that chemicals are causing on the environment [33].…”
Section: Pesticidesmentioning
confidence: 99%
“…For example, nicotine at high levels can reduce bees' fitness, although at lower, naturally occurring levels, there are no apparently detrimental effects and the substance can even be beneficial (Kohler et al, 2012). Other toxins produced in flowers have also been shown to reduce the life span of bees in laboratory settings, depending on the dose (Santoro et al, 2004;Rother et al,2009;Rocha-Neto et al,2011). Rother et al (2009) tested the effects of ricinine (a toxic compound of Ricinus communis -Euphorbiaceae) on bees of the species Apis mellifera and Scaptotrigona postica and observed that A. mellifera had a high mortality within 72 hours for two of three concentrations tested (0.05 and 0.1%), while S. postica presented high mortality rate only after 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Other toxins produced in flowers have also been shown to reduce the life span of bees in laboratory settings, depending on the dose (Santoro et al, 2004;Rother et al,2009;Rocha-Neto et al,2011). Rother et al (2009) tested the effects of ricinine (a toxic compound of Ricinus communis -Euphorbiaceae) on bees of the species Apis mellifera and Scaptotrigona postica and observed that A. mellifera had a high mortality within 72 hours for two of three concentrations tested (0.05 and 0.1%), while S. postica presented high mortality rate only after 14 days. Santoro et al (2004) demonstrated that A. mellifera was also susceptible to tannins of Stryphnodendron spp.…”
Section: Discussionmentioning
confidence: 99%